2002
DOI: 10.1177/0739986302024003003
|View full text |Cite
|
Sign up to set email alerts
|

Self-Esteem in the Adaptation of Spanish-Speaking Adolescents: The Role of Immigration, Family Conflict, and Depression

Abstract: Acultural context model was employed in studying self-esteem group differences within a Spanish-speaking sample of adolescents. Acculturation patterns for Spanish-speaking subgroups show differences in the way that they will fit into American society. Depression, parent-child conflict, and discrimination influenced individual self-esteem, along with school achievement and motivation. Regression analyses were employed to partition and study the variance of the above predictors. The cultural contexts of five gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
34
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 28 publications
6
34
0
Order By: Relevance
“…Studies of Hispanic adolescents in immigrant families have consistently found an inverse association between parent-adolescent conflict and psychological well-being. According to studies of Mexican-origin adolescents, parent-adolescent conflict is related to higher levels of depression and anxiety and of lifetime alcohol use, as well as marijuana abuse and deviant behavior (Marsiglia, Kulis, Parsai, Villar, & Garcia, 2009;McQueen, Getz, & Bray, 2003;Pasch et al, 2006), and similar findings have been reported among Hispanic adolescents of diverse national origin (Behnke, Plunkett, Sands, & Bámaca-Colbert, 2011;Kuhlberg et al, 2010;Pedro & Zady, 2002).…”
Section: Parent-adolescent Conflict and Psychological Well-beingmentioning
confidence: 65%
See 1 more Smart Citation
“…Studies of Hispanic adolescents in immigrant families have consistently found an inverse association between parent-adolescent conflict and psychological well-being. According to studies of Mexican-origin adolescents, parent-adolescent conflict is related to higher levels of depression and anxiety and of lifetime alcohol use, as well as marijuana abuse and deviant behavior (Marsiglia, Kulis, Parsai, Villar, & Garcia, 2009;McQueen, Getz, & Bray, 2003;Pasch et al, 2006), and similar findings have been reported among Hispanic adolescents of diverse national origin (Behnke, Plunkett, Sands, & Bámaca-Colbert, 2011;Kuhlberg et al, 2010;Pedro & Zady, 2002).…”
Section: Parent-adolescent Conflict and Psychological Well-beingmentioning
confidence: 65%
“…Higher family cohesion was found among adolescents in Hispanic families compared to those in non-Hispanic families (Baer & Schmitz, 2007), and a positive association between cohesion and Hispanic adolescents' psychological well-being has been reported (Lorenzo-Blanco, Unger, Baezconde-Garbanati, Ritt- Olson, & Soto, 2012). A well-studied risk factor for all adolescents is parent-adolescent conflict, and it has been found to be negatively associated with psychological well-being among Hispanic adolescents specifically (Kuhlberg, Peña, & Zayas, 2010;Pasch et al, 2006;Pedro & Zady, 2002). Few studies, however, have investigated factors that might ameliorate the effect of parent-adolescent conflict.…”
mentioning
confidence: 99%
“…Though rarely used, such a design is becoming increasingly important because the Mexican-American population shows vast diversity and has migrated to widely divergent geographic locations and communities across the U.S. Emerging evidence suggests that risk and protective processes associated with Latino cultural adaptation can vary widely depending on the extent to which traditional culture is supported, treated with hostility, or absent within receiving communities (Gonzales et al 2009;Portes and Zady 2002). Thus, failure to account for cultural differences at the community level may limit understanding of how unique social processes operating within diverse communities can offset or amplify family and community economic conditions.…”
Section: Study Limitations and Contributionsmentioning
confidence: 99%
“…In fact, several studies posit that experiencing discrimination negatively affects self-esteem among Chinese American adolescents (Diaz, Ayala, Bein, Henne, & Marin, 2001;Greene et al, 2006;Rivas-Drake, Hughes, & Way, 2008;Swim, Hyers, Cohen, & Ferguson, 2001), Moroccan and Turkish adolescents in the Netherlands (Verkuyten, 1998), as well as Latino/a adolescents, including Dominican youth (Greene et al, 2006;Portes & Zady, 2002;Shorey, Cowan, & Sullivan, 2002).…”
Section: Discrimination Stress and Self-esteemmentioning
confidence: 99%